Impact of drought and salt stress on the biosynthesis of alkaloids in Chelidonium majus L. (August 2018) - Yahyazadeh, Mahdi; Meinen, Rieke; Hänsch, Robert; Abouzeid, Sara; Selmar, Dirk
Abstract: When plants are exposed to various stress situations, their alkaloid concentration frequently is enhanced. This well-known phenomenon is presumably due to a passively enhanced rate of biosynthesis, caused by greatly elevated concentrations of NADPH in stressed plants. Here, we used Chelidonium majus L. plants, which accumulate high concentrations of dihydrocoptisine in their leaves, to study the impact of drought and salt stress on the biosynthesis and accumulation of alkaloids. In comparison to well-watered controls, in the transcriptome of the gene encoding the key enzyme in alkaloid biosynthesis, stylopine synthase, is enhanced in stressed C. majus plants. If we presuppose that increased transcript levels correlate with increased enzymatic activity of the gene products, these data indicate, for the first time, that stress-related increases in alkaloid concentration might not only be caused by the well-known stress-related passive shift, but may also be due to an enhancement of enzymatic capacity. Graphical abstract: Image 1 Highlights: The main alkaloid in leaves of Chelidonium majus is dihydrocoptisine. Its concentration increased in response to salt and drought stress. This increase is correlated by an enhancement of the expression of stylopine synthase. The stress related enhanced reduction status passively increased the biosynthesis. Thus, in addition to the passive shift, biosynthesis is also actively up-regulated.